2015
DOI: 10.1093/femsec/fiv165
|View full text |Cite
|
Sign up to set email alerts
|

Adding mucins to anin vitrobatch fermentation model of the large intestine induces changes in microbial population isolated from porcine feces depending on the substrate

Abstract: Adding mucus to in vitro fermentation models of the large intestine shows that some genera, namely lactobacilli, are dependent on host-microbiota interactions and that they rely on mucosal layers to increase their activity. This study investigated whether this dependence on mucus is substrate dependent and to what extent other genera are impacted by the presence of mucus. Inulin and cellulose were fermented in vitro by a fecal inoculum from pig in the presence or not of mucin beads in order to compare fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…2B; Table S1). This finding is noteworthy as its presence in the swine gut microbiota was reported only recently (31, 32). The Rikenellaceae family itself is a relatively new taxonomic classification within the Bacteroidales order, with only three genera currently described (33).…”
Section: Resultssupporting
confidence: 63%
“…2B; Table S1). This finding is noteworthy as its presence in the swine gut microbiota was reported only recently (31, 32). The Rikenellaceae family itself is a relatively new taxonomic classification within the Bacteroidales order, with only three genera currently described (33).…”
Section: Resultssupporting
confidence: 63%
“…This might be related to a better adaptation of the microbiota from the HSF-inoculum to the pre-digested PEC and/or a potential modification of PEC by the pre-digestion, as suggested by the PEC flocculation observed under the acidic conditions of the first step of the pre-digestion. These results are in agreement with the changes previously observed by Tran et al (2016) in the gas production, VFA molar proportions and microbiota profile when mucins (another fraction of the endogenous substances) were added to in vitro batch fermentations, although only minor interactions were detected between mucins and the incubated substrates (cellulose and inulin). Further studies would be required to assess whether supplementation of the substrate with other quantitatively relevant endogenous substances (like mucins) should be implemented, as previous in vivo and in vitro studies have reported a high fermentability of mucins (Abad-Guamán et al, 2015;Marounek et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Controversy observed in mice studies and clinical interventions in humans is also consistent with this idea. A recent work shows opposite patterns upon mucin usage as substrate by Lactobacillus and Akkermansia (56), thereby suggesting that trophic interactions may underlie, at least in part, these opposite trends of both microorganisms. Actually, a negative effect on Akkermansia levels in the gut upon administration of a probiotic mixture was observed when Lactobacillus , but not other probiotic bacteria, were added to the mixture (57).…”
Section: Discussionmentioning
confidence: 99%